Android-based shopping skill for mentally-disable student - Agustina Sri Purnami; Mulyoto Mulyoto; Bekti Winoto (Journal of Education and Learning (EduLearn), 2020)
This study aimed to develop an Android-based learning media to improve shopping skills in retarded students. The research method was the design validation stage which is part of the research development. The instruments used in this study were (1) the practicality of the research product questionnaire, and (2) the validation sheet to measure the validity of the research product. The data analysis technique was to determine the average rating of research products, then the average was stated qualitatively in four categories which are very high, high, medium, and invalid. The results showed that the Android-based application media to support shopping skills has been validated by experts and practitioners in the good category.